Effects of crown architecture and stand structure on light absorption in mixed and monospecific Fagus sylvatica and Pinus sylvestris forests along a productivity and climate gradient through Europe. (19th June 2017) - Forrester, David Ian; Ammer, Christian; Annighöfer, Peter J.; Barbeito, Ignacio; Bielak, Kamil; Bravo‐Oviedo, Andrés; Coll, Lluis; del Río, Miren; Drössler, Lars; Heym, Michael; Hurt, Václav; Löf, Magnus; et al.
Abstract: When tree‐species mixtures are more productive than monocultures, higher light absorption is often suggested as a cause. However, few studies have quantified this effect and even fewer have examined which light‐related interactions are most important, such as the effects of species interactions on tree allometric relationships and crown architecture, differences in vertical or horizontal canopy structure, phenology of deciduous species or the mixing effects on tree size and stand density. In this study, measurements of tree sizes and stand structures were combined with a detailed tree‐level light model (Maestra) to examine the contribution of each light‐related interaction on tree‐ and stand‐level light absorption at 21 sites, each of which contained a triplet of plots including a mixture and monocultures of Fagus sylvatica and Pinus sylvestris (63 plots). These sites were distributed across the current distribution of these species within Europe. Averaged across all sites, the light absorption of mixtures was 14% higher than the mean of the monocultures. At the whole community level, this positive effect of mixing on light absorption increased as canopy volume or site productivity increased, but was unrelated to climate. At the species population or individual tree levels, the mixing effect on light absorption resulted from light‐related interactions involving vertical canopy structure, stand density, the presence of a deciduous species ( F. sylvatica ), as well as the effects of mixing on tree size and allometric relationships between diameter and height, crown diameter and crown length. The mixing effects on light absorption were only correlated with the mixing effects on growth for P. sylvestris, suggesting that the mixing effects on this species were driven by the light‐related interactions, whereas mixing effects on F. sylvatica or whole community growth were probably driven by non‐light‐related interactions. Synthesis . The overall positive effect of mixing on light absorption was the result of a range of light‐related interactions. However, the relative importance of these interactions varied between sites and is likely to vary between other species combinations and as stands develop. Abstract : The overall positive effect of mixing on light absorption was the result of a range of light‐related interactions. However, the relative importance of these interactions varied between sites and is likely to vary between other species combinations and as stands develop.